Valve turning towards on-cycle in cobalt-catalyzed Negishi-type cross-coupling - Xu Luo; Dali Yang; Xiaoqian He; Shengchun Wang; Dongchao Zhang; Jiaxin Xu; Chih-Wen Pao; Jeng-Lung Chen; Jyh-Fu Lee; Hengjiang Cong; Yu Lan; Hesham Alhumade; et al. (Nature Communications, 2023)
Abstract Ligands and additives are often utilized to stabilize low-valent catalytic metal species experimentally, while their role in suppressing metal deposition has been less studied. Herein, an on-cycle mechanism is reported for CoCl2bpy2 catalyzed Negishi-type cross-coupling. A full catalytic cycle of this kind of reaction was elucidated by multiple spectroscopic studies. The solvent and ligand were found to be essential for the generation of catalytic active Co(I) species, among which acetonitrile and bipyridine ligand are resistant to the disproportionation events of Co(I). Investigations, based on Quick-X-Ray Absorption Fine Structure (Q-XAFS) spectroscopy, Electron Paramagnetic Resonance (EPR), IR allied with DFT calculations, allow comprehensive mechanistic insights that establish the structural information of the catalytic active cobalt species along with the whole catalytic Co(I)/Co(III) cycle. Moreover, the acetonitrile and bipyridine system can be further extended to the acylation, allylation, and benzylation of aryl zinc reagents, which present a broad substrate scope with a catalytic amount of Co salt. Overall, this work provides a basic mechanistic perspective for designing cobalt-catalyzed cross-coupling reactions.